Sling exercise for chronic low back pain: a systematic review and meta-analysis. - Yu-Shan Yue; Xu-Dong Wang; Bin Xie; Zhong-Han Li; Bing-Lin Chen; Xue-Qiang Wang; Yi Zhu (PLoS ONE)
Background Trials on sling exercise (SE), commonly performed to manage chronic low back pain (LBP), yield conflicting results. This study aimed to review the effects of SE on chronic LBP. Methods The randomized controlled trials comparing SE with other treatments or no treatment, published up to August 2013, were identified by electronic searches. Primary outcomes were pain, function, and return to work. The weighted mean difference (WMD) and 95% confidence interval (CI) were calculated, using a random-effects model. Results Risk of bias was rated as high in 9 included trials, where some important quality components such as blinding were absent and sample sizes were generally small. We found no clinically relevant differences in pain or function between SE and other forms of exercise, traditional Chinese medical therapy, or in addition to acupuncture. Based on two trials, SE was more effective than thermomagnetic therapy at reducing pain (short-term: WMD -13.90, 95% CI -22.19 to -5.62; long-term: WMD -26.20, 95% CI -31.32 to -21.08) and improving function (short-term: WMD -10.54, 95% CI -14.32 to -6.75; long-term: WMD -25.75, 95% CI -30.79 to -20.71). In one trial we found statistically significant differences between SE and physical agents combined with drug therapy (meloxicam combined with eperisone hydrochloride) but of borderline clinical relevance for pain (short-term: WMD -15.00, 95% CI -19.64 to -10.36) and function (short-term: WMD -10.00; 95% CI -13.70 to -6.30). There was substantial heterogeneity among the two trials comparing SE and thermomagnetic therapy; both these trials and the trial comparing SE with physical agents combined with drug therapy had serious methodological limitations. Interpretation Based on limited evidence from 2 trials, SE was more effective for LBP than thermomagnetic therapy. Clinically relevant differences in effects between SE and other forms of exercise, physical agents combined with drug therapy, traditional Chinese medical therapy, or in addition to acupuncture could not be found. More high-quality randomized trials on the topic are warranted.